Approaching Hypothetical RbTl in Experiments and Theory - X-ray Structure Determination of Cs1-xRbxTl (x = 0.18, 0.42) and a Solid Solution K1-xRbxTl (x ≤ 0.69) - Schwinghammer, Vanessa F; Khan, Saleem A; Tiefenthaler, Susanne M; Kovářík, Tomáš; Minár, Ján; Gärtner, Stefanie (Inorganic chemistry, 2025)
Although the binary alkali metal thallides ATl with A = Li, Na, K, and Cs have been reported in the literature, binary RbTl at ambient pressure is still missing. Experiments with a 1:1 ratio of Rb:Tl, either according to Zintl's procedure in low-temperature experiments in liquid ammonia or classical solid-state synthesis at high temperature, did not result in the desired product. Therefore, several ternary compositions with mixtures of K/Rb and Cs/Rb have been prepared. For K/Rb mixtures, a solid solution in the KTl structure type, up to a proportion of 69% rubidium, could be obtained. Site occupancy preferences for rubidium on the alkali metal sites in the KTl type are observed in experiments and supported by theoretical calculations. In contrast to Rb/K mixtures being realizable in the KTl structure type, Rb/Cs mixtures did not allow for the isolation of materials according to the CsTl structure type. Instead, two new monoclinic compounds could be isolated (Cs0.82Rb0.18Tl: C2/c, a = 14.4136(4) Å, b = 11.1678(3) Å, c = 40.8013(11) Å, β = 96.353(2)°, V = 6527.4(3) Å3; Cs0.58Rb0.42Tl: C2/c, a = 14.2610(3) Å, b = 11.1116(2) Å, c = 27.5589(7) Å, β = 104.056(2)°, V = 4236.30(17) Å3). Detailed DFT calculations on both binary and mixed cation systems were performed and support the experimental results.